Acute effects of physical exercise on cognitive function and neurotrophins in patients with type 1 diabetes: A systematic review - Emanuele Zanardo; Giulia Quinto; Francesca Battista; Federica Duregon; Marco Vecchiato; Chiara Bergia; Kirk Erickson; Andrea Ermolao; Daniel Neunhaeuserer (Heliyon)
Background: Type 1 diabetes mellitus (T1DM) is associated with cognitive decline. In contrast, higher levels of neurotrophins, such as brain-derived neurotrophic factor (BDNF), may be associated with better brain health. Physical exercise has been associated with elevated levels of BDNF and consequently improved cognitive function, but whether this association is found in T1DM remains unresolved. The aim of this systematic review was to evaluate the acute effect of physical exercise on cognitive function and BDNF levels in patients affected by T1DM. Methods: MEDLINE, Cochrane Library (CENTRAL database), EMBASE and SPORTDiscus were screened by 2 independent reviewers, who selected studies that analysed acute effects of physical exercise in patients with T1DM on BDNF levels or cognitive function tests before and after exercise. Studies in humans and English written were included. The quality of these studies was assessed using the respective Cochrane Risk of Bias tool. Results: After identifying 507 articles, 4 studies including 78 participants were analysed. Two studies were non-randomized clinical trials, the others were crossover trials. Selected studies performed different exercise intervention protocols, evaluating both high and moderate intensity training. BDNF levels were found higher after exercise in all studies. Cognitive function tests resulted also improved after the training intervention. Conclusions: In subjects with T1DM, preliminary evidence suggests that exercise training might increase plasma BDNF levels and ameliorate cognitive deficits. However, scientific evidence is still very limited and there is a significant need for further research to clarify the possible positive neurocognitive effects of exercise in T1DM.